The impact of phosphatidylserine exposure on cancer cell membranes on the activity of the anticancer peptide HB43. (20th November 2021) - Herrera‐León, Claudia; Ramos‐Martín, Francisco; Antonietti, Viviane; Sonnet, Pascal; D'Amelio, Nicola
Abstract : HB43 (FAKLLAKLAKKLL) is a synthetic peptide active against cell lines derived from breast, colon, melanoma, lung, prostate, and cervical cancers. Despite its remarkable spectrum of activity, the mechanism of action at the molecular level has never been investigated, preventing further optimization of its selectivity. The alternation of charged and hydrophobic residues suggests amphipathicity, but the formation of alpha‐helical structure seems discouraged by its short length and the large number of positively charged residues. Using different biophysical and in silico approaches we show that HB43 is completely unstructured in solution but assumes alpha‐helical conformation in the presence of DPC micelles and liposomes exposing phosphatidylserine (PS) used as mimics of cancer cell membranes. Membrane permeabilization assays demonstrate that the interaction leads to the preferential destabilization of PS‐containing vesicles with respect to PC‐containing ones, here used as noncancerous cell mimics. ssNMR reveals that HB43 is able to fluidify the internal structure of cancer‐cell mimicking liposomes while MD simulations show its internalization in such bilayers. This is achieved by the formation of specific interactions between the lysine side chains and the carboxylate group of phosphatidylserine and/or the phosphate oxygen atoms of targeted phospholipids, which could catalyze the formation of the alpha helix required for internalization. With the aim of better understanding the peptide biocompatibility and the additional antibacterial activity, the interaction with noncancerous cell mimicking liposomes exposing phosphatidylcholine (PC) and bacterial mimicking bilayers exposing phosphatidylglycerol (PG) is also described. Abstract : HB43 is a synthetic peptide active against various cancer cells. HB43 gets internalized in cancer cells mimetic bilayers, destabilizing their internal structure whereas the interaction with erythrocyte mimicking bilayers is much weaker. The exposition of phosphatidylserine carboxylate groups creates an accessible negatively charged surface able to catalyze the formation of the alpha helix, required for HB43 internalization.